A mixture of persistent organic pollutants relevant for human exposure inhibits the transactivation activity of the aryl hydrocarbon receptor in vitro. (November 2019) - Doan, T.Q.; Berntsen, H.F.; Verhaegen, S.; Ropstad, E.; Connolly, L.; Igout, A.; Muller, M.; Scippo, M.L.
Abstract: While humans are exposed to mixtures of persistent organic pollutants (POPs), their risk assessment is usually based on a chemical-by-chemical approach. To assess the health effects associated with mixed exposures, knowledge on mixture toxicity is required. Several POPs are potential ligands of the Aryl hydrocarbon receptor (AhR), which involves in xenobiotic metabolism and controls many biological pathways. This study assesses AhR agonistic and antagonistic activities of 29 POPs individually and in mixtures by using Chemical-Activated LUciferase gene eXpression bioassays with 3 transgenic cell lines (rat hepatoma DR-H4IIE, human hepatoma DR-Hep G2 and human mammary gland carcinoma DR-T47-D). Among the 29 POPs, which were selected based on their abundance in Scandinavian human blood, only 4 exerted AhR agonistic activities, while 16 were AhR antagonists in DR-H4IIE, 5 in DR-Hep G2 and 7 in DR-T47-D when tested individually. The total POP mixture revealed to be AhR antagonistic. It antagonized EC50 TCDD inducing AhR transactivation at a concentration of 125 and 250 and 500 fold blood levels in DR-H4IIE, DR-T47-D and DR-Hep G2, respectively, although each compound was present at these concentrations lower than their LOEC values. Such values could occur in real-life in food contamination incidents or in exposed populations. In DR-H4IIE, the antagonism of the total POP mixture was due to chlorinated compounds and, in particular, to PCB-118 and PCB-138 which caused 90% of the antagonistic activity in the POP mixture. The 16 active AhR antagonists acted additively. Their mixed effect was predicted successfully by concentration addition or generalized concentration addition models, rather than independent action, with only two-fold IC50 underestimation. We also attained good predictions for the full dose-response curve of the antagonistic activity of the total POP mixture. Graphical abstract: Image 1 Highlights: Mixed exposure is more realistic for human exposure to POPs. Total POP mixture relevant for human exposure is AhR antagonistic. Chlorinated compounds are the drivers of the activity of the total POP mixture. PCB-118 and PCB-138 contribute for 90% of the total POP mixture effect. Dose-response curve of the mixture was predicted successfully by CA and GCA models. Abstract : A mixture of persistent organic pollutants relevant to human exposure antagonized the transcriptional activity of the Aryl hydrocarbon receptor in vitro, whose activity could be predicted.